ANALYSIS OF SCHOOL BULLYING BEHAVIOR IN STUDENTS HIGH CLASS STATE 23 PRIMARY SCHOOL BANDA ACEH - Kenusi, Afrilliana; Israwati, Israwati; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2024)
Cases of school bullying in Indonesia occur in almost every school institution, not only in high schools and middle schools, but also at the elementary school level, many cases have occurred which have resulted in great trauma to the victims. This research aims to analyze school bullying behavior in high class students at SD Negeri 23 Banda Aceh. This research approach uses a qualitative approach with descriptive research type. The subjects in this research were teachers in grades IV, V, and VI, and students in grades IV, V, and VI who were perpetrators and victims of bullying. Data collection techniques in this research used observation and interviews. Data analysis techniques are carried out starting from the data reduction, data display, and verification/conclusion stages. Based on the research results, it was found that there were 3 forms of bullying behavior carried out by high class students, namely: 1) physical bullying, 2) verbal bullying, and 3) relational bullying. Factors that cause bullying behavior among high class students include: 1) Family factors, 2) Personality factors, 3) Peer factors, 4) Mass media factors, and 5) School factors. The impacts of bullying behavior include anxiety, fear, trauma (fear of going to school), revenge, and heartache. The teacher's way of dealing with bullying is by providing advice personally and to all students, giving punishments/sanctions to perpetrators of bullying, and guiding students who behave in bullying ways. Based on the results of this research, it can be concluded that school bullying behavior is aggressive behavior carried out repeatedly by a person or group of students who have power/strength over other students who are weaker with the aim of hurting, where there are forms of bullying, factors- causal factors, negative impacts on victims, and teachers' ways of dealing with bullying behavior.